2011
DOI: 10.1542/neo.12-5-e252
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Heart Surgery: Evaluation of Risk Factors

Abstract: Neonatal heart surgery directed at the prompt anatomic and physiologic restoration of the patient who has congenital heart disease has largely developed in the past 2 decades. To obtain the best possible results and minimize the multiple risks involved with such surgery, various considerations must be taken into account, including the institution where the surgery occurs, the human resources available, and the particular characteristics of the newborn. An accurate statistical analysis of the surgical outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
1
5
0
Order By: Relevance
“…The assessment of the RACHS-1 as a predictor of hospital mortality by ROC curve showed area of 0.860 95% CI 0.818 to 0.902 with P <0.0001 and statistically significant and comparable to that found in the literature [9] (Fig. 2].…”
Section: Fig 1 -Linear Regression Between Expected and Observed Mortsupporting
confidence: 82%
See 2 more Smart Citations
“…The assessment of the RACHS-1 as a predictor of hospital mortality by ROC curve showed area of 0.860 95% CI 0.818 to 0.902 with P <0.0001 and statistically significant and comparable to that found in the literature [9] (Fig. 2].…”
Section: Fig 1 -Linear Regression Between Expected and Observed Mortsupporting
confidence: 82%
“…In linear regression between the RACHS-1 risk classification and hospital mortality it is clearly demonstrated that there are statistically significant correlation and that is a valid instrument for use in our country [9].…”
Section: Fig 1 -Linear Regression Between Expected and Observed Mortmentioning
confidence: 79%
See 1 more Smart Citation
“…However, with this improved survival rate, an increase in morbidity due to surgical and post-surgical complications has been seen [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Although we have had occasional articles on surgical topics (eg, "The EXIT Strategy" in 2005, [1] "Minimal Access Surgery in the Neonate" in 2006, [2] and "Neonatal Heart Surgery: Evaluation of Risk Factors" in 2011, [3] with the most recent example being the article titled "Neonatal Airway Obstruction: An Overview of Diagnosis and Treatment" in the March 2013 issue [4]), this month we focus on neonatal surgery.…”
mentioning
confidence: 99%